Assessment of different methods of sowing of vegetable cowpea to harness productivity and profitability potential - Chaturvedi, A.K.; Pandey, Rakesh; Chaudhary, R. P.; Prasad, R. (Annals of Agricultural Research, 2016)
Cowpea is one of the important leguminous vegetables, an important source of nutrients and highquality protein to cereal based diets. The variety 'Kashi Kanchan' with high production potentialdeveloped from Indian Institute of Vegetable Research, Varanasi is preferred by farmers. Threemethods of sowing with recommended package practices were assessed in order to achieve theproductivity potential. Highest number of pods plant–1 (27.6 and 27.6), plant height (58.3 and 59.5cm) and yield (135.5 and 125.4 q ha–1) was recorded in raised bed method of sowing during 2012and 2013, respectively. Similarly, highest net return `98300 ha–1 and `95740 ha–1 with highest B:Cratio 3.64 and 3.27 was also observed in raised bed method of sowing during 2012 and 2013,respectively.Key words: Cowpea